(untitled) (Portuguese Journal of Family Medicine and General Practice, 2014)
Objectives: To compare the risk of venous thromboembolism (VTE) among users of fourth generation oral contraceptives and previous generations of combined oral contraceptives (COC), and to analyze the possible correlations between age, body mass index (BMI) and duration of COC use and the risk of VTE. Study design: Case-control study. Setting: Centro Hospitalar do Alto-Ave, Hospital de Braga and Unidade Local de Saúde do Alto Minho. Participants: A sample of 257 women was analyzed, including 122 with a previous history of VTE and 135 without a history of VTE. Methods: The medical records of women with a history of VTE, which occurred between 2010 and 2013, were reviewed. Women of using COC at the time of the VTE were identified as cases. The controls were women using COC followed in a family planning clinic, without a history of VTE. Results: Fourth generation COC do not increase the risk of VTE compared to older COC (OR = 1.77; IC95 0.93-3.38; p = 0.083). There was no correlation between BMI and the risk of VTE (OR = 1.53; IC95 0.76-3.06; p = 0.234). Age (OR = 1.5; IC95 1.02-1.09; p = 0.001) and duration of COC use (OR = 2.41; IC95 1.19-4.87; p = 0.014) were associated with VTE. Conclusions: The risk of VTE depends on age and duration of COC use. Due to limitations of the study, the finding of relative safety of fourth generation COC for the risk of VTE compared to older contraceptives must be interpreted with caution